The Politics and Science of Prevision Governing and Probing the Future - Wenger, Andreas; Jasper, Ursula; Dunn Cavelty, Myriam (CSS Studies in Security and International Relations, 2020)
"This book inquires into the use of prediction at the intersection of politics and academia, and reflects upon the implications of future-oriented policymaking across different fields. The volume focuses on the key intricacies and fallacies of prevision in a time of complexity, uncertainty and unpredictability. The first part of the book discusses different academic perspectives and contributions to future-oriented policymaking. The second part discusses the role of future knowledge in decision-making across different empirical issues such as climate, health, finance, bio- and nuclear weapons, civil war, and crime. It analyses how prediction is integrated into public policy and governance, and how in return governance structures influence the making of knowledge about the future. Contributors integrate two analytical dimensions in their chapters- the epistemology of prevision and the political and ethical implications of prevision. In this way, the volume contributes to a better understanding of the complex interaction and feedback loops between the processes of creating knowledge about the future and the application of this future knowledge in public policy and governance. This book will be of much interest to students of security studies, political science, sociology, technology studies and IR."